Ikonografia Hatszepsut i Totmesa III w świątyni Hatszepsut w Deir el-Bahari jako odbicie relacji między współwładcami - Sankiewicz, Marta (My University, 2014)
Ikonografia królewska w świątyni Hatszepsut w Deir el-Bahari oddaje niezwykłe okoliczności jednoczesnego panowania dwóch legalnych władców: Hatszepsut i Totmesa III. Postawiono hipotezę, że Hatszepsut za pomocą różnych zabiegów dotyczących aranżacji przedstawień pokazywała Totmesa III na drugorzędnej pozycji. Wyróżniono pary cech o charakterze wartościującym, oparte głównie na hierarchii stron świata, z których jedna była ważniejsza i spodziewana u Hatszepsut, a druga podrzędna i miała odnosić się do Totmesa III. Następnie przeanalizowano wszystkie wizerunki Hatszepsut i Totmesa III ze ścian Deir el-Bahari. Szczególny nacisk został położony na wyróżnione pary komplementarnych przedstawień współwładców. Podsumowanie wykazało, że faktycznie większość cech dominujących została przypisana przedstawieniom Hatszepsut, podczas gdy Totmesa III charakteryzowały elementy drugorzędne.

Royal iconography in the temple of Hatshepsut AT Deir el-Bahri reflects unusual circumstances of simultaneous reign of two legitimate rulers: Hatshepsut and Thutmose III. The hypothesis was proposed that Hatshepsut by using various ways of the arrangement of representations showed Thutmose III in the secondary position. Pairs of evaluative features were established, mainly based on the hierarchy of the cardinal points, of which one was more important and expected for Hatshepsut, and the other secondary and had to refer to Thutmose III. Then analyzed all the images of Hatshepsut and Thutmose III of the walls of Deir el-Bahari. Particular emphasis was placed on the highlighted pairs of complementary representations of co-rulers. Summary showed that in fact most dominant features has been assigned to representations of Hatshepsut, while Thutmose III was characterized by elements of the secondary meaning.
Iconography of Hatshepsut and Thumose III in the Temple of Hatshepsut at Deir el-Bahari as a reflection of the relationship between co-rulers
Wydział Historyczny
Keywords: Hatszepsut; Hatshepsut; Totmes III; Thutmose III; Nowe Państwo; New Kingdom; Deir el-Bahari; Królewska ikonografia; Royal iconography